An Immersive Olfactory VR Framework: Integrating Virtual Field Environments with Real-Time Scent Delivery via MQTT - Silva, Meryck F. B. Da; Diniz, Pedro K.; Carvalho, Rodrigo M. De; Barros, Ana C. De A.; A. Neto, Miguel C. De; Silva Junior, Jonas G. Da; Faria, Gustavo P. De; Silva, Thalles H. B. Da; Coronado, Angelo; Silva, Cleiver B. Da; Galvão Filho, Arlindo Rodrigues; Andrade, Carolina H. (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2025: Anais do XXVII Simpósio de Realidade Virtual e Aumentada, 2025)
This paper introduces an immersive olfactory virtual reality (OVR) framework that integrates AI-driven olfactory segmentation, a high-fidelity scent delivery device, and a photorealistic virtual environment. It leverages semantic segmentation and depth estimation to generate olfactory masks from 360-degree panoramas, enabling real-time context-aware scent delivery synchronized with user perspective and proximity. Implemented within Unreal Engine and validated through controlled VR scenes, the framework provides a comprehensive solution for enhancing multisensory realism and adaptability in virtual reality.